EFEKTIVITAS PROBLEM BASED LEARNING UNTUK MENGOPTIMALKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Yenni, Yenni; Krisky Mulyani, Yunda; Sukmawati, Rika (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2017)
This research is motivated by the low ability of students' mathematical problem solving. The purpose of research to determine the effect of Problem Based Learning (PBL) model of learning to improve students' mathematical problem solving abilities. This research was conducted at SMP Alijtihad II Kutabaru Tangerang Regency. The research method used is quasi experiment with design of non equivalent control group design. Sampling was done by using purposive sampling technique, student of class VIIIB as experiment class using PBL model and class VIIID students as control class with conventional method. The instrument used is a test to measure the ability to solve mathematical problems in the form of a description. Test instrument data were analyzed using the t-test and the Mann-Whitney U Test. Based on the result of calculation using t-test at 0.05 significance level, obtained tcount ? ttable (3,3841 ? 1,9966), so that PBL learning model can influence student's mathematical problem solving ability. The Mann-Whitney U Test showed that Zhitung ? Ztable (2.82 ? 1.92) thus enhanced mathematical problem-solving abilities in the class using the PBL model better than the conventional method. The improvement of students' highest mathematical problem solving abilities in the PBL class is on the indicators of planning the completion, whereas in the conventional class is on the indicators understand the problem